2019
DOI: 10.1002/jnr.24542
|View full text |Cite
|
Sign up to set email alerts
|

Control of cortical synapse development and plasticity by MET receptor tyrosine kinase, a genetic risk factor for autism

Abstract: Dysregulated synapse development is posited to underlie the pathophysiology of many neurodevelopmental and neuropsychiatric disorders, including autism spectrum disorder (ASD), schizophrenia, and major depression. These complex brain disorders all share a major developmental etiology, and a common feature that disease onset and progression occurs during early brain development and matu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 153 publications
(268 reference statements)
0
11
0
Order By: Relevance
“…In line with these studies, forebrain-specific MET cKO mice show altered circuit formation and function including synaptic plasticity. Consistently, animal studies and clinical imaging have provided evidence that disrupted MET signaling produces functional as well as morphological alterations in neurons in those brain regions implicated in ASD endophenotypes (reviewed in Peng et al, 2013;Eagleson et al, 2017;Ma and Qiu, 2019).…”
Section: Implications Of Hgf-met Gene Mutations In Nddsmentioning
confidence: 87%
See 1 more Smart Citation
“…In line with these studies, forebrain-specific MET cKO mice show altered circuit formation and function including synaptic plasticity. Consistently, animal studies and clinical imaging have provided evidence that disrupted MET signaling produces functional as well as morphological alterations in neurons in those brain regions implicated in ASD endophenotypes (reviewed in Peng et al, 2013;Eagleson et al, 2017;Ma and Qiu, 2019).…”
Section: Implications Of Hgf-met Gene Mutations In Nddsmentioning
confidence: 87%
“…MET has an important role in neuron architecture construction and synapse maturation, as described in previous sections. The reduced gene expression or deletion of MET in vivo in mice results in altered synapse maturation (reviewed in Ma and Qiu, 2019 ). A strong evidence of HGF-MET axis importance in the human development of nervous system comes from some studies that reveal a genetic implication of HGF and MET genes in some NDDs such as autism spectrum disorder (ASD), schizophrenia, and non-syndromic hearing loss.…”
Section: Implications Of Hgf-met Gene Mutations In Nddsmentioning
confidence: 99%
“…Recent work from our laboratory and others have demonstrated that prenatally, subsets of developing vagal motor neurons express the Met receptor tyrosine kinase (MET) (Isabella et al, 2020;Kamitakahara et al, 2017;Wu and Levitt, 2013), positioning it as a candidate for distinguishing motor neuron types. MET is a pleiotropic receptor, known to be important in synapse maturation and critical period development in the cerebral cortex (Chen et al, 2020;Ma and Qiu, 2019;Xie et al, 2016) and for the differentiation of several different motor neuron pools in the brainstem and spinal cord (Caton et al, 2000;Ebens et al, 1996;Tallafuss and Eisen, 2008;Wong et al, 1997). For example, upon binding its only known ligand, hepatocyte growth factor (HGF), MET confers neuronal survival in developing spinal motor neurons innervating the pectoralis minor muscle (Lamballe et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other ASD‐risk genes have also been found to regulate synaptogenesis and plasticity. One such example is provided in this issue, where Ma and Qiu focus on the human MET gene, which encodes a receptor tyrosine kinase (Ma & Qiu, 2019). MET is a prominent autism risk gene, with single nucleotide polymorphisms associated with ASD found in different populations around the world.…”
mentioning
confidence: 99%